New Conditions for the Development of the “Great Game” in the Arctic and Priorities of the Current Concept Foreign Policy of Russia - S. Yu. Kozmenko; A. S. Kozmenko (Евразийская интеграция: экономика, право, политика, 2024)
With the next expansion of NATO to the east, when Finland became the 31st  member of the alliance, the Arctic party of the “Great Game” began to unfold in addition to the European party, which continues today in Ukraine. These parties directly or indirectly cover the coast and waters of three Russian seas  — the Black, Baltic and Barents   — and logically fit into the global confrontation between maritime and continental civilizations, known as the geopolitical epic “The Great Game”. In the same year, 2023, a new Concept of Russian foreign policy was adopted, which especially highlights the Arctic among regional areas. This is how new conditions for the development of the Arctic are created against the backdrop of the Arctic party of the “Great Game”.Aim . The purpose of the article is to identify the features of Russia’s positioning in the Arctic in new conditions/Tasks. To achieve the formulated goal, the following tasks are being solved: to identify probable external challenges and threats to Russia in the Western Arctic and to propose measures to counter the latter.Methods. The work uses the methodological approach of strategic planning in combination with the tools of spatial economics and the theory of new economic geography. This makes it possible to coordinate the target dominants of defense and economic activities in the Western Arctic in new geo-economic and political conditions.Conclusions . The aggravation of the geopolitical situation on the sidelines of the “Great Game” now directly affects the Arctic, and the global confrontation between two civilizations has come directly to the western borders of Russia in the Arctic region   — this  is how a   direct threat to our country has formed.